KESULITAN DAN STRATEGI BAGI PEMELAJAR CHINA DALAM PEMBELAJARAN FONETIK INDONESIA KELAS DARING NOMOR 20 SEBAGI CONTOHNYA - Zhang Lidong (Seminar Internasional Riksa Bahasa, 2021)
ABSTRAK Affected by COVID-19, many Chinese students choose to learn Indonesian online. Phonetics is the foundation for learning Indonesian, which is very important for every beginner. However, many Chinese students often encounter many difficulties or often make many mistakes when learning phonetics. Based on my own teaching experience, the author uses observation and analysis to analyze the problems that often occur in the Indonesian phonetic learning process of elementary classes 20, and summarize the reasons for the above problems, namely (1) like to compare with Hanyu Pinyin and English, and is deeply pronounced by native speakers Influence; (2) failing to pronounce according to the teacher’s demonstration; (3) passive mentality, not reviewing after class. In response to the above problems, the author proposes solutions, namely (1) the teacher must explain carefully and demonstrate correctly; (2) guide and correct on time; (3) encourage students to practice more and increase their interest in learning; (4) should pay attention to the combination of teaching pronunciation and teaching vocabulary dan (5) Students must actively cooperate with teachers and correct their attitudes and learning methods. The purpose of writing this article is to help Chinese students learn Indonesian and improve BIPA teaching in China.